Paths and Dead Ends of Critical Race Theory - Bratina, Boris R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper introduces the reader to the fundamentals of Critical Race Theory, which is highly influential today. The author accomplishes this not only by simply introducing the reader to the most important aspects of this relatively new teaching but also by examining each of them critically. Throughout his presentation, the author discusses all of the major influences on the development of this theory, starting with Marxism, (post)structuralism, and legal practice as a source of facticity. According to him, this academic-activist movement has at least three basic theoretical propositions: 1) the thesis about institutionalized racism in the United States from its founding to the present, 2) the thesis that race is not a biological but a cultural concept and, accordingly, the advocacy of anti-essentialism, and 3) thesis and decision to expand Critical Race Theory by introducing minorities (most notably, sexual minorities) into the game. The paper critically examines the idea that racism stems from skin colour, as well as the movement’s decision to seek support outside the circle of racism-related problems. This expansion blunts both CRT’s theoretical edge and its practical application, as evidenced by the fate of anti-racist and emancipatory movements. Finally, the author demonstrates how the entire movement conforms to the ruling racial system.